2019
DOI: 10.3791/59194
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Epithelial Enteroid Model of Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a devastating disease of newborn infants. It is characterized by multiple pathophysiologic alterations in the human intestinal epithelium, leading to increased intestinal permeability, impaired restitution, and increased cell death. Although there are numerous animal models of NEC, response to injury and therapeutic interventions may be highly variable between species. Furthermore, it is ethically challenging to study disease pathophysiology or novel therapeutic agents direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Necrotizing enterocolitis (NEC) is a devastating intestinal disease of premature infants (4,5,21). Despite decades of research, the complex pathophysiology is incompletely understood, and despite advances in neonatal care, the mortality remains high (21).…”
Section: Introductionmentioning
confidence: 99%
“…Necrotizing enterocolitis (NEC) is a devastating intestinal disease of premature infants (4,5,21). Despite decades of research, the complex pathophysiology is incompletely understood, and despite advances in neonatal care, the mortality remains high (21).…”
Section: Introductionmentioning
confidence: 99%
“…23 Ares et al have also reported a human epithelial model of NEC that involves culturing human organoids after isolation of intestinal stem cells from patients undergoing bowel resection. 37 The authors demonstrate that administration of LPS in the growth media of organoids leads to changes in histology, genetic and protein expression, as well as an inflammatory response resembling human NEC including increased mRNA and protein expression of TLR4. 37 Development of NEC is preceded by changes in the intestinal microbial population including reduced diversity and colonization by specific species.…”
Section: Neonatal Intestinal Organoids As Ex Vivo Models Of Necmentioning
confidence: 99%
“…37 The authors demonstrate that administration of LPS in the growth media of organoids leads to changes in histology, genetic and protein expression, as well as an inflammatory response resembling human NEC including increased mRNA and protein expression of TLR4. 37 Development of NEC is preceded by changes in the intestinal microbial population including reduced diversity and colonization by specific species. 38 Hence, it is essential to have a clear understanding of the role of microbes in the development of the neonatal intestine, as well as in pathogenesis of NEC.…”
Section: Neonatal Intestinal Organoids As Ex Vivo Models Of Necmentioning
confidence: 99%
“…The journey from the crypt to detachment from the tip takes approximately 4 to 5 days (Vachon et al, 2000; van der Flier and Clevers, 2009). Crypt cells from the human small intestine have been successfully cultured as primary monolayer cells (Browning and Trier, 1969;Panja, 2000;Benoit et al, 2010;Beaulieu and Ménard, 2012) as well as three-dimensional organoids (enteroids) as an in vitro model for the evaluation of intestinal physiology and diseases including the evaluation of major histocompatibility complex class II regulation (Wang et al, 2018;Wosen et al, 2019), interaction of the enterocytes with pathogenic microbiota (In et al, 2019;Stewart et al, 2020), modeling infectious diarrheal diseases (Kovbasnjuk et al, 2013;Foulke-Abel et al, 2014, elucidation of pathogenesis of intestinal diseases such as inflammatory bowel disease (Rees et al, 2019) and necrotizing enterocolitis (Senger et al, 2018;Ares et al, 2019), and the elucidation of the cell and molecular pathways controlling stem cell maturation into enterocytes (Das et al, 2015;Mahe et al, 2015;Schilderink et al, 2016). As of this writing, there are no reports defining the expression and activity of drug metabolizing enzymes in human enteroids.…”
Section: Stem Cell-derived Modelsmentioning
confidence: 99%